The complete chloroplast genome of Rhododendron kawakamii (Ericaceae). Issue 9 (2nd September 2021) - Wang, Zheng-Feng; Chang, Li-Wan; Cao, Hong-Lin
Abstract: Rhododendron kawakamii is endemic in Taiwan island and is a unique and epiphytic species. Here, we report its complete chloroplast genome. The length of the R. kawakamii chloroplast genome is 230, 777 bp, with a large single-copy region of 146, 155 bp, a small single-copy region of 72, 082 bp, and a pair of inverted repeat regions (IRA) of 6, 270 bp each. The genome contains 77 protein-coding genes, 29 transfer RNA genes, and four ribosomal RNA genes. In addition, the genome contains 81 simple sequence repeats. Phylogenetic analysis revealed that R. kawakamii is genetically related to R. datiandingense .